2009
DOI: 10.1002/ajh.21526
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with hydroxyurea in a patient compound heterozygote for a high oxygen affinity hemoglobin and β‐thalassemia minor

Abstract: Enhanced oxygen delivery to tissues has been shown to improve endurance performance [1]. This has led to widespread abuse of erythropoiesis-stimulating agents (ESA) in elite sport. It is conceivable that athletes have even learned how to continue illicit ESA doping [2]. This possibility has fuelled the search for novel methods to detect and deter ESA abuse using ''indirect'' markers. It is now widely accepted that drugs influence gene expression [3,4]. In this study, we envisage its use as a means to detect ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, a treadmill study showed no difference in exercise tolerance in the patient before and after reduction of PCV level (8). A patient with compound heterozygosity for Hb Regina [β96(FG3)Leu!Val, CTG>GTG] and β þ -thal, developed hepatosplenomegaly and renal vein thrombosis (9). This patient was treated with hydroxyurea resulting in an increase in Hb F, shift of p50 and a decrease in red cell volume, and the treatment led to an improvement in "general status."…”
Section: Compound Heterozygosity For Hb Johnstown and Hb Lbwmentioning
confidence: 96%
See 1 more Smart Citation
“…However, a treadmill study showed no difference in exercise tolerance in the patient before and after reduction of PCV level (8). A patient with compound heterozygosity for Hb Regina [β96(FG3)Leu!Val, CTG>GTG] and β þ -thal, developed hepatosplenomegaly and renal vein thrombosis (9). This patient was treated with hydroxyurea resulting in an increase in Hb F, shift of p50 and a decrease in red cell volume, and the treatment led to an improvement in "general status."…”
Section: Compound Heterozygosity For Hb Johnstown and Hb Lbwmentioning
confidence: 96%
“…There are a few exceptions including the patient with Hb Regina described above (9). Two of six patients reported by Percy et al (16) were said to have had thrombosis, but no details were given, thus it is unclear whether these patients had additional thrombophilic risks.…”
Section: Compound Heterozygosity For Hb Johnstown and Hb Lbwmentioning
confidence: 99%
“…Hb Regina was first identified in a Canadian man in his late 20s of Scandinavian descent with erythrocytosis in 1985 8. Subsequently, a German family was described in 1991,9 and the third reported case was a Caucasian male in his late 30s who also had co-inheriting β-thalassaemia trait ( HBB :c.93–21G>A previously known as IVS1-110 G/A) 10. In the heterozygous cases, the variant constituted between 30% and 40% of the total Hb,8 while the double heterozygous case had the variant as the predominant Hb (85%) with absent HbA0 (10).…”
mentioning
confidence: 99%